2009
DOI: 10.3892/or_00000513
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of radiofrequency ablation in colorectal lung metastases: Single center experience

Abstract: Abstract. This study was undertaken to evaluate long-term results of radiofrequency (RF) ablation in patients with colorectal lung metastases and to stratify patients benefitting from lung RF ablation. Lung RF ablation was performed in 78 patients with 198 colorectal lung metastases. Safety, local tumor progression, and survival were evaluated retrospectively. The mean follow-up period after the 140 lung RF ablation sessions was 24.6±7.6 months. Pneumothorax and pleural effusion requiring chest tube placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 23 publications
7
54
0
1
Order By: Relevance
“…The 5-year survival rates after lung RFA have been reported to be 27-61% for NSCLC [11][12][13] and 20-69% for metastatic lung cancer [14][15][16]. Our results seemed to be comparable with these previously reported findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The 5-year survival rates after lung RFA have been reported to be 27-61% for NSCLC [11][12][13] and 20-69% for metastatic lung cancer [14][15][16]. Our results seemed to be comparable with these previously reported findings.…”
Section: Discussionsupporting
confidence: 83%
“…However, some patients cannot undergo surgery because of poor respiratory function, advanced age, or comorbid disease. Recently, radiofrequency ablation (RFA) of the lung for patients who are not surgical candidates has been reported to achieve comparable results to surgical resection [11][12][13][14][15][16][17][18][19]. However, the availability of this treatment in Japan and re- ports on its outcomes from this country are limited because of lack of coverage within the national health insurance system.…”
Section: Introductionmentioning
confidence: 99%
“…A significant difference between the survival curves was associated with large ([3 cm) or small (B3 cm) tumor diameter. In a study that included patients with colorectal lung metastases, a 5-year overall survival rate of 35% was reported [62]. Two other prognostic factors were found to be carcinoembryonic antigen levels and extrapulmonary disease.…”
Section: Outcomes and Effectivenessmentioning
confidence: 98%
“…The 1-year and 3-year overall survival rates were 83.9% (95% confidence interval [95% CI], 92.7%-75.2%) and 56.1% (95% CI, 70.5%-41.7%), respectively, and the median survival time was 38.0 months in all patients. 2 In the article by Chua et al, the survival curve was plotted only between patients treated with and without adjunctive systemic chemotherapy (the median survival times were 59 months and 21 months, respectively, as shown in Figure 5 in their article), 1 although the presence of extrapulmonary metastases at the time of RFA treatment, identified as a negative predictive factor for patient survival in both studies, was found to be significantly dominant (P ¼ .019 using the chi-square test) in our study cohort compared with that of Chua et al (24 of 78 patients and 16 of 100 patients, respectively). 1,2 This finding might also support the benefit of systemic chemotherapy as an adjunct to RFA in patients with pulmonary metastases from colorectal cancer in multimodality therapy.…”
mentioning
confidence: 99%